2019
DOI: 10.1016/j.jvs.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic benefits of advanced pneumatic compression devices in patients with phlebolymphedema

Abstract: This analysis indicates significant benefits attributable to FLX compared with alternative compression therapies that can help reduce the notable economic burden of phlebolymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The prevailing opinion that flat-knit garments provide intrinsically better containment than other garments was challenged by a study published by the International Compression Club (ICC) which concluded that the dynamic stiffness of circular and flat knit fabrics are not different. 42 Although flat knit may be a heavier fabric, the study concluded that once a piece of fabric has a stretch to it (which both flat and circular knit have), then the stiffness is not very high. We believe that the above analysis provides a good working understanding of the circular and flat knit garments.…”
Section: Results and Commentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevailing opinion that flat-knit garments provide intrinsically better containment than other garments was challenged by a study published by the International Compression Club (ICC) which concluded that the dynamic stiffness of circular and flat knit fabrics are not different. 42 Although flat knit may be a heavier fabric, the study concluded that once a piece of fabric has a stretch to it (which both flat and circular knit have), then the stiffness is not very high. We believe that the above analysis provides a good working understanding of the circular and flat knit garments.…”
Section: Results and Commentsmentioning
confidence: 99%
“… 40 Two commercial claims-based studies demonstrated significant reduction in healthcare costs associated with the use of an advanced SPC device; one was in a mixed population of cancer and non-cancer associated lymphedema of both the upper and lower extremities, 41 and the other was in a population of phlebolymphedema patients, almost all of whom had either C5 or C6 CVI. 42 In both cases, the cost reduction was primarily driven by the reduced requirement for inpatient and outpatient treatment for cellulitis as well as reduced use of physical and occupation therapy.…”
Section: Results and Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of studies demonstrating the benefits of advanced PCGT, particularly with regard to the overall improvement in economic burden to the health care system when compared to CDT. [7][8][9] However, only one paper has looked at feasibility and outcomes of the device in the head and neck population. In addition to subjective assessments of overall patient satisfaction with the device, this paper by Mayrovitz et al exclusively used external facial and neck measurements as its principle objective outcome.…”
Section: Introductionmentioning
confidence: 99%